A study on job stress among staff in UiTM Jengka Pahang / Hazirah Kamarizaman, Noor Faeizah Amat Nan and Nor Farah Hana Amir Sharifuddin - Kamarizaman, Hazirah; Amat Nan, Noor Faeizah; Amir Sharifuddin, Nor Farah Hana (2012)
Job life is one of the important parts of our daily lives which cause a great deal of stress. Workplace stress is the harmful physical and emotional response that occurs when there is a poor match between job demands and the capabilities, facilities, and needs of the staff in UiTM Jengka, Pahang. The primary purpose of this study was to look at the level of job stress. Job stress consist of three variable that were workload pressure, performance pressure and role ambiguity. Previous research has been discussed in this study that will help the researcher to find out the level of stress and identify factors that will cause the stress occur of the staff in UiTM Jengka Pahang. The study focuses on the staff were in staff from library, facilities, HEA (Hal Ehwal Akademik) and security units in UiTM Jengka Pahang. Based on finding from data collected, show that workload pressure were the most contribute to job stress among staff in UiTM Jengka, Pahang.